Literature review: manifestation of skin lesion on COVID-19 - Firmansyah, Yohanes; Tan, Sukmawati Tansil; Elizabeth, Jessica; Lauren, Christopher (International Journal of Research in Dermatology, 2021)
New cases of pneumonia, which spread rapidly and are deadly, have spread throughout the world. This disease is known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or corona virus disease 2019 (COVID-19) with a viral etiology in the form of novel coronavirus 2019 (2019-nCoV). This disease has extensive clinical manifestations starting from the lungs, hematology system, heart, nerves, reproduction, and the skin. The thing to be aware of is that the skin manifestations in the form of atypical lesions are often found in COVID-19. Common skin manifestations on COVID-19 are erythema-edema with vesicles or pustules (pseudo-chilblain), vesicular eruption, maculopapular rash, urticaria, and livedo lesion. This literature review discusses comprehensively what kind of skin lesions can be suspected of being part of a COVID-19 infection. This literature review is useful for increasing the awareness of doctors about COVID-19 infection and may help in early diagnose of COVID-19 infection and prevent further transmission.